Islamic Financial Literacy and Financial Behavior on Investment Intention - Roemanasari, Febrita; Sabela, Jenny; Rusgianto, Sulistya (Jurnal Ilmu Ekonomi Terapan, 2022)
The low level of financial literacy, especially Islamic financial literacy which can affect individual readiness to plan finances and accept risks in relation to financial investments. This research aims to determine the effect of Islamic financial literacy and financial behavior on investment intentions.. The research used in this research is quantitative research with the questionnaire method on google form to respondents as well as using secondary data derived from literature and the results of previous studies then the survey results were processed using SPSS and analyzed and interpreted to conclude the findings. The result is that Islamic financial literacy, financial risk tolerance and behavioral biases have a positive effect on investment intentions.